1440. Potential Impact of Routine Use of 13-Valent Pneumococcal Conjugate Vaccine on Hospitalizations for Pneumonia among Older Adults in Canada. (26th November 2018) - Vojicic, Jelena; Dion, Stephane; Isturiz, Raúl E; Laferriere, Craig; Major, Maria; Nepal, Rajeev M; Suaya, Jose A; McLaughlin, John M
Abstract: Background: In Canada, 13-valent pneumococcal conjugate vaccine (PCV13) was licensed for the prevention of vaccine-type (VT) pneumonia in adults in July 2015. Herd effects stemming from the routine pediatric PCV13 program have historically led to reductions in VT disease in older adults, and there is currently no recommendation for a routine age-based PCV13 program for this age group. However, recent data suggest these indirect effects may have plateaued, leaving a persistent and substantial burden of potentially preventable pneumococcal disease in older adults. We evaluated the potential impact of PCV13 immunization program for Canadian adults aged ≥65 years on hospitalizations for community-acquired pneumonia (CAP). Methods: We constructed a mathematical model based on Canada-specific burden of disease estimates and published estimates of PCV13 effectiveness and durability. We estimated the number of hospitalizations averted as the product of (i) the size of the Canadian population aged ≥65 years, (ii) the incidence of all-cause CAP, (iii) the proportion of CAP that is VT, (iv) PCV13 effectiveness, and (v) the duration of protection for PCV13 over a 5-year time horizon. We assumed that rates of all-cause CAP, the proportion of VT CAP, and PCV13 effectiveness remained constant over the 5-year assessment period. We assumed a 5% annual all-cause mortality rate in the overall population. We estimated hospital days averted as the product of hospitalizations averted and median length of stay. Model assumptions are summarized in Table 1. Results: Based on model assumptions, PCV13 use in Canadian adults aged ≥65 years would lead to an annual rate reduction of 62 (11–77) hospitalizations per 100, 000 persons, per year. This reduction, applied to the entire Canadian population of older adults, would avert an estimated 17, 274 (3, 037–21, 711) hospitalizations and 138, 192 (24, 298–173, 690) hospital days over a 5-year period. Conclusion: Despite herd effects from the routine pediatric program, direct PCV13 immunization of older adults in Canada could result in considerable additional reduction in hospitalizations for pneumonia. Disclosures: J. Vojicic, S. Dion, R. E. Isturiz, C. Laferriere, M. Major, R. M. Nepal, and J. A. Suaya: Pfizer: Employee and Shareholder, Benefits and stock and Salary; J. M. McLaughlin, Pfizer: Employee, Salary.